1986
DOI: 10.2307/3898755
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Livestock Trampling under Intensive Rotation Grazing on Soil Hydrologic Characteristics

Abstract: Infiltration rate decreased significantly and sediment production increased significantly on a site with a silty clay surface soil devoid of vegetation following periodic trampling typical of intensive rotation grazing systems. The deleterious impact of livestock trampling generally increased as stocking rate increased. Damage was augmented when the soil was moist at the time of trampling. Thirty days of rest were insufficient to allow hydrologic recovery. Soil bulk density, aggregate stability, aggregate size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
131
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 31 publications
3
131
2
1
Order By: Relevance
“…Studies have been conducted to determine relationships between various soil moisture conditions and soil hydraulic properties after grazing (Edmond 1962, Warren et al 1986b. It is believed that there is a greater chance for compaction in wet soils than in dry soils.…”
Section: Immediate Effects Of Grazingmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have been conducted to determine relationships between various soil moisture conditions and soil hydraulic properties after grazing (Edmond 1962, Warren et al 1986b. It is believed that there is a greater chance for compaction in wet soils than in dry soils.…”
Section: Immediate Effects Of Grazingmentioning
confidence: 99%
“…led to degradation of soil physical characteristics (Clary 1995), which in turn can lead to altered hydrologic properties (Bryant et al 1972), increased sediment production (Warren et al 1986b), and a decline in vegetation productivity and vigor (Dadkhah and Gifford 1980, Leininger and Trlica 1986).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research conducted on Western rangeland conditions has shown that overgrazing of forages or the increased space between bunchgrasses near surface waters decreases the effectiveness of the forage to reduce the velocity of overland water flow (Temple 1982;Masterman and Thorne 1992), thereby increasing the risk of sediment and nutrient loading of the streams (Alderfer and Robinson 1947;Warren et al 1986). Overgrazing may be caused by high stocking rates (Manley et al 1997), long grazing duration (Krueger et al 2002), or congregation of cattle near streams (Tate et al 2003), particularly during seasons with low vegetation productivity (Miner et al 1992).…”
Section: Introductionmentioning
confidence: 99%